Performance analysis of a three-blade spiral horizontal axis wind turbine with an aspect ratio of 0,116 - Wiwit Suprihatiningsih; Abdul Hamid; Adji Nur Fadilah (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
The horizontal-axis wind turbine (TASH) is a wind energy technology that can generate electricity, but its performance still has to be improved. To determine how much an aspect ratio affects wind turbine performance, this study used a horizontal-axis wind turbine with three spiral blades and an aspect ratio of 0,116. The primary performance metrics of horizontal-axis wind turbines with three spiral blades and an aspect ratio of 0,116 are to be measured and examined in this work. Understanding how aspect ratio affects voltage (volts), current (amperes), torque (τ), turbine rotational speed (rpm), and in line with wind speed (ρw) in the process of generating electrical energy is the specific goal. A horizontal-axis wind turbine with three spiral blades and an aspect ratio of 0,116 will be constructed and tested in a controlled setting as part of this research's experimental methodology. The systematic measurement of essential performance characteristics, such as wind speed, torque, turbine rotational speed, voltage, and current, will provide a comprehensive understanding of the wind turbine's ability to generate electrical energy. The TASH experiment 3 spiral blades with an aspect ratio of 0,116 yielded the highest value when tested using a planetary gearbox at 24,23 rpm, 53,09 V of voltage, 1,25 A of electric current, and 30,94 Nm of torque at 5,0 m/s of wind speed. In the calculation of the power coefficient, torque coefficient, and tip speed ratio, the minimum value obtained in the test without a planetary gearbox was 0,0231 at wind speed 2,5 m/s, 0,2183 at wind speed 2,5 m/s, and 0,1059 at wind speed 2,5 m/s. The minimum value is obtained in the TASH test without a planetary gearbox with a rpm value of 105,89 rpm, Voltage 8,60V, Electric Current 0,05A, and Torque 2,85Nm at wind speed 2,5 m/s. A planetary gearbox with a power coefficient of 0,4713 at a wind speed of 4.5 m/s, a torque coefficient of 0,6813 at a wind speed of 4,0 m/s, and a tip speed ratio of 0,7525 at a wind speed of 5,0 m/s was used to test the system and determine the maximum value.